Governance models for historical hospitals: evidence from Italy - Martina Giusti; Ilaria Elisa Vannini; Niccolò Persiani (BMC, 2024)
Abstract Many hospitals and health care organizations over the centuries have inherited handcrafts of artistic value, objects of worships, donations from pilgrims, votive offerings, legates as a result of their centuries-old activity in the social and health care of their community. The value of these artistic assets and the role in the territory of these hospitals have transformed them into cultural heritage over time, introducing the issue of the coexistence of cultural and care management. Therefore, the aim of this paper is to identify governance models of what we will call historical hospitals, that is, hospitals that because of their history, their assets, and their artistic heritage, far from being places only dedicated to provision of health care services represent cultural heritage. To pursue this research objective, five Italian historical hospitals were selected and identified as significant case studies for their historic and artistic relevance. Through the analysis of these case studies the paper identifies models of governance of historical hospitals and the reasons of their adoption.